Peran Wanita dalam Keluarga Perspektif Al-Qur’an Surat Al Ahzab Ayat 33 Studi Pemikiran Quraish Shihab - Moch. Azis Qoharuddin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
A woman is a mukallaf (a person who has responsibility) like men, where women also receive orders and prohibitions from Allah swt, are rewarded and get punished, women are not enemies of men nor are they rivals but as a complement to him, women are part of men and men are part of women. And every human life must yearn for a happy family inside and out, calm, peaceful, mutual respect and appreciation, full of love and affection, as if a enchanting beautiful garden is heaven, Baiti Jannati if there is heaven in this world, that is a happy family. On the other hand, if there is hell in this world, it is a broken family. Quraish Shihab explains the meaning of this verse that Allah in general has told that to look beautiful in the life of the world towards things that can please, including women and children, begins by mentioning women as the first who will please men.